2002
DOI: 10.1161/01.cir.0000027564.55739.b1
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Ablation of Idiopathic Ventricular Fibrillation

Abstract: Background-Ventricular fibrillation is the main mechanism of sudden cardiac death. The feasibility of eliminating recurrent episodes by catheter ablation has not been reported. Methods and Results-Twenty-seven patients without known heart disease (13 men, 14 women, 41Ϯ14 years of age) were studied after being resuscitated from recurrent (10Ϯ12) episodes of primary idiopathic ventricular fibrillation; 23 had received a defibrillator. The first initiating beat of ventricular fibrillation had an identical electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
517
2
19

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 602 publications
(553 citation statements)
references
References 34 publications
15
517
2
19
Order By: Relevance
“…Currently, there is no cure for VF, with only rudimentary treatment options available; thus, sudden cardiac death from VF remains a major worldwide health problem 3, 4. The Purkinje system is implicated in the genesis of primary VF,5, 6, 7 with radiofrequency ablation successfully treating this lethal arrhythmia by targeting triggers, such as a premature ventricular beat emanating from Purkinje tissue 7, 8, 9, 10. However, current radiofrequency ablation approaches to the Purkinje fibers have limitations, particularly because they can only be applied in a point‐to‐point manner, which is tedious and time‐consuming.…”
mentioning
confidence: 99%
“…Currently, there is no cure for VF, with only rudimentary treatment options available; thus, sudden cardiac death from VF remains a major worldwide health problem 3, 4. The Purkinje system is implicated in the genesis of primary VF,5, 6, 7 with radiofrequency ablation successfully treating this lethal arrhythmia by targeting triggers, such as a premature ventricular beat emanating from Purkinje tissue 7, 8, 9, 10. However, current radiofrequency ablation approaches to the Purkinje fibers have limitations, particularly because they can only be applied in a point‐to‐point manner, which is tedious and time‐consuming.…”
mentioning
confidence: 99%
“…Haissaguerre et al reported 27 patients who had idiopathic VF, 23 of which had VF arising from the Purkinje conducting system. They reported an 89% success rate for RFA (mean follow-up of 24 months) [4]. These studies support the rationale of pursuing RFA in treating idiopathic VF that is refractory to medical therapy.…”
Section: Discussionmentioning
confidence: 65%
“…Over the past 6 to 8 years, there has also been the description and growing recognition of patients with VF that has a focal origin. The majority of these seem to originate from the right ventricular outflow tract (RVOT) [3][4][5]. Other foci include sites in the right ventricle (RV) outside the RVOT and sites in the left ventricle (LV).…”
Section: Introductionmentioning
confidence: 99%
“…This special role played by Purkinje fibers in heart combined with their spatially intermittent isolation from the ventricular mass make them potential arrhythmogenic sources as illustrated by mapping studies in idiopathic ventricular fibrillation, long-QT and Brugada syndromes, and following myocardial infarction [33][34][35]. Several groups have explored the link between Ca 2+ waves and afterdepolarizations in Purkinje fiber cells as a possible mechanism for triggered arrhythmias [36][37][38].…”
mentioning
confidence: 99%